Studi RegeDerasi daD Produksi Protoplas Mesofil Daun Beberapa KlOD TanamaD Kentang (Solanum tuberosum L.) . - Asnawatr, ,; Wattimenal, G. A.; Machmud, M.; Purwito, Agus (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2002)
The objectives of these experiments were to obtain medium composition to enlarge leaf size for protoplast production and to obtain medium composition for plant regeneration. The result showed that the best medium to produce the larger leaves was medium MS with double concentration of macronutrients without hormone supplemented with Morel vitamins, 3% (w/v) sucrose and. 7 g/l agar. This medium produced leaves with diameter of 1.44 cm comparing to control medium MS with 0.67 cm in diameter. Medium MS containing 0.1 mg/l 1AA, 0.5 mg/l Zeatin and 0.5 mg/l GA3 was able to regenerate vigorous shoots of 7 clones. Protoplast isolation of 5 clones using enzyme composition containing 0.5 % cellulase Onozuka RS, 0.05 %, pectolyase Y-23, 0.05 % MES, 9.1 % mannitol and pH 5.5, without CP W medium produced protoplast with variable yield from 10.50 x 1oJ protoplast/g leaves for Atlantic to 46.58x 1oJ protoplast/gforBF15.   Keyword: Leaves size, Plant regeneration, Potato, Protoplast i